Beneficial Properties and Sustainable Use of a Traditional Medicinal Plant: Griffonia simplicifolia - Amirhossein Nazhand; Alessandra Durazzo; Massimo Lucarini; Fabrizia Guerra; Angélica Gomes Coêlho; Eliana B. Souto; Daniel Dias Rufino Arcanjo; Antonello Santini (Challenges, 2024)
Since ancient times, medicinal plants have been a universal source of biologically active substances with high potential for the treatment of various diseases and disorders. For centuries, traditional communities have often relied on medicinal plants to treat health problems. Therefore, accurate information is required and knowledge about traditional medicinal plants requires evaluation, and great attention should be given to the possible integration of these plants as therapeutic agents or as complements to conventional pharmacological therapies in the healthcare system. Recently, Griffonia simplicifolia (DC.) Baill., initially used as a holistic remedy, has attracted attention from many researchers and consumers because of its multiple health-promoting effects. This growing interest prompted us to give an updated review of the botanical, geographical, historical, and therapeutic potentials of Griffonia simplicifolia (DC.) Baill. in terms of its in vitro and in vivo health effects, nutritional uses, and possible applications in line with biodiversity and sustainability concepts. This paper also presents a quantitative research analysis of the published studies related to this plant that are available in the literature. To retrieve the publications related to this plant, a bibliographic search was carried out using the Scopus database. The bibliometric data were extracted and processed using VOSviewer software (v.1.6.16, 2020). Technological possible applications in terms of patents request presented was also performed. A total of 1386 publications, from the year 1970 to the year 2021, were obtained by the literature search, and these had been collectively cited 38,805 times. The large amount of literature data available documents the interest in this plant’s use as a tool for integrating traditional holistic healing approach, e.g., using plants, herbs, and holistic remedies, into the healthcare system as supporting tools and/or therapeutic agents, which is a current worldwide challenge.